NURSING ENGLISH TEACHING MATERIAL: A STUDY OF STUDENTS’ PERCEPTION - Risman Wanci; Sujariati Sujariati; Yassir Mallapiang (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
A teaching material needs to be evaluated to get better results than the previous one, and among the forms of evaluation is to involve students to discover their perceptions regarding the teaching material that has been tried out or used. This study aims to discover nursing students’ perception towards nursing English teaching materials that have been developed and tested at a private nursing college. The goal is to get positive input regarding the teaching material to become material for the next revision. The design of this research is a survey study. The sample of this study was 40 nursing students at a private nursing campus in Makassar, Indonesia. The result shows that the interval scores of students’ perception were in the Strongly Positive and Positive category. There were 33 (83%) of the respondents who had strongly positive perceptions, and 7 (18%) of the respondents had positive perceptions; none of the respondents had neutral, negative, or strongly negative perceptions. In addition, that the mean score of students’ perception was 45.93, with a standard deviation was 4.091. It shows that the students had strongly positive perceptions toward nursing English teaching material based on task-based instruction. The authors admit that there are still things that need to be improved in the development of teaching materials, but based on this research data, the authors can conclude that nursing students receive these teaching materials.